Reconstruction of Paleoforest in Gunungsewu Karst Area in the Period of Human History - Lies Rahayu Wijayanti Faida; Sutikno Sutikno; Chafid Fandeli; Sunarto Sunarto (Jurnal Ilmu Kehutanan)
This research was carried out in Gunungsewu Karst area, Gunungkidul District from Kanigoro to Wediombo. The main objectives of this research are (1) to identify floristic history and (2) to reconstruct the palaeoforest profiles in the area. Palaeoecobotanical approach is used as the basis for the reconstruction of palaeoforest. Descriptive-explanatory methods were used to explore, interpret, and reconstruct floristic tracks from pollen analysis, radiocarbon dating, vegetation analysis, and also human cultural history. Explanatory approach was used to describe collected data, to compare, to find association, and to explain the research finding. Hypothetical tests were done by deductive-inductive logics, using general theories for basic foundation to be verified by facts from the fields. This research resulted in three types of flora from Prehistoric times to the present, that is tropical mountainous forest of 16,894±440 - 9,296±140 years BP, tropical rainforests in 9,296±140 - 1,753±90 years BP, and monsoonal forests in 1,753±90 years BP until now. The Euphorbiaceae was the oldest flora occupied the area, existed between 16,894±440 years BP until now, while the Moraceae which is known as the karstic floral identity began to be found since 9,296±140 years BP. Reconstruction of palaeoforest in human prehistory provides information that the tropical mountain forests had inhabited the area before the era of Keplek, then entering the era of Keplek until Ngrijangan the tropical rainforest occupied this area. In the era of Klepu, the forest has been turned into the monsoon type and this type persists through history until now. Cultural traits of prehistoric subsistence can explain that change in the types of flora is not caused by anthropogenic factors, but due to climate change triggered by the ice age expiration that marked the end of the Pleistocen.